Non-coding RNAs in heart failure: epigenetic regulatory mechanisms and therapeutic potential - Ren, Yubo; Zhao, Bomeng; Lv, Luo; Yang, Jingyuan; Nan, Xiangting; Li, Bao; Yang, Bin (Frontiers in Genetics, 2025)
Heart failure represents the terminal stage of diverse cardiovascular disorders and continues to impose a heavy global burden despite advances in therapy. Beyond classical neurohormonal and hemodynamic pathways, recent studies underscore the central role of non-coding RNAs in orchestrating epigenetic remodeling that drives hypertrophy, fibrosis, and cardiomyopathy. In this review, we synthesize evidence into an integrative “ncRNAs–epigenetics–cardiomyopathy” working model that connects upstream non-coding RNAs regulation with chromatin dynamics and downstream pathological remodeling. We integrate evidence showing how microRNAs, long non-coding RNAs, and circular RNAs reshape transcriptional networks through interactions with DNA methylation, histone, and RNA modifications. Differential non-coding RNAs signatures across heart failure phenotypes, comorbidities, and complications are further highlighted, underscoring their potential utility in patient stratification and biomarker discovery. We also evaluate therapeutic frontiers that extend beyond single-target interventions toward multi-layered approaches, including antisense oligonucleotides, CRISPR/dCas9-mediated epigenome editing, and exosome- or nanoparticle-based delivery systems. Although translational barriers remain considerable, especially in terms of specificity, safety, and clinical validation, these strategies illustrate the potential of targeting the ncRNAs–epigenetic axis to advance precision medicine in heart failure.